Kto pierwszy przemówił? Uwarunkowania morfologiczne mowy ludzkiej - Kujawa, Betina (Polskie Towarzystwo Antropologiczne, 1995)
WHO SAID AS THE FIRST? MORPHOLOGICAL DETERMINANTS OFHUMAN SPEECH. The evolution of human speech was probably involved into development of brain structures responsible for cultural behaviour, specially tool-making. Moreover, it has been sugested that only Homo erectus species had the speech apparatus formed the way which allowed to articulate some sounds.
WHO SAID AS THE FIRST? MORPHOLOGICAL DETERMINANTS OF HUMAN SPEECH